TRANSFORMASI PENDIDIKAN ISLAM ANAK DI SEKOLAH DALAM PERSPEKTIF PSIKOLOGI DI ERA REVOLUSI INDUSTRI 4.0 - Khoirotus Silfiyah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2021)
This research aims to find out the transformation of school and education in the perspective of psychology in era 4.0. This research uses the method of reseacrh library approach. That is, in this study using books, previous research journals, articles in the form of magazines or newspapers, and other scientific writings. The results show that teachers and children are required to be ready in the face of the transformation of education and school that is happening now. However, the fact that the impact of learning transformation that all uses technology, especially gadgets psychological perspective actually makes children easily experience emotions that are less stable, concentration decreases and frequent tantrums. Seeing these conditions, it takes good synergy between teachers, parents, and the community to participate in order to be able to give birth to an independent, intelligent generation and able to meet a better future.